Peranan Bumdes dalam Peningkatan Pendapatan Asli Daerah Desa Baha Kabupaten Badung - I Putu Satya Guna Dharma; I Gusti Bagus Suryawan; I Made Aditya Mantara Putra (Jurnal Konstruksi Hukum, 2023)
BUMDes is a pillar of economic activity in the village that functions as a social and commercial institution. The development of the welfare of rural communities requires strategies that are in accordance with regional conditions which cover all aspects of the potential of the region or village. Based on this background, this research discusses the role of BUMDes in increasing local revenue in Baha Village, Badung Regency and how BUMDes efforts overcome obstacles in increasing PAD in Baha village, Badung Regency by using an empirical legal research method that examines law that is conceptualized as real treatment. The formation of BUMDes is a way to take advantage of laws that give authority to village governments to innovate in village development. The establishment of village-owned enterprises is accompanied by efforts to strengthen capacity and is supported by regional (district/village) policies that participate in facilitating and protecting village community businesses from the threat of competition from large investors. villages independently, so that they can improve the village economy, and can improve the welfare of the community. The existence of BUMDes is expected to reduce poverty levels so that the community's economy can increase.